2022
DOI: 10.3390/toxics10020044
|View full text |Cite
|
Sign up to set email alerts
|

PFAS Molecules: A Major Concern for the Human Health and the Environment

Abstract: Per- and polyfluoroalkyl substances (PFAS) are a group of over 4700 heterogeneous compounds with amphipathic properties and exceptional stability to chemical and thermal degradation. The unique properties of PFAS compounds has been exploited for almost 60 years and has largely contributed to their wide applicability over a vast range of industrial, professional and non-professional uses. However, increasing evidence indicate that these compounds represent also a serious concern for both wildlife and human heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
64
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(90 citation statements)
references
References 292 publications
(361 reference statements)
2
64
0
Order By: Relevance
“…The PFAS regulation rules differ among European countries; for example, in Denmark, the use of PFAS in paper and board food packaging has been banned since July 2020, and no French fries bags exhibit PFAS; but in Czechia, these items recently showed highly persistent PFAS levels [ 4 ]. Despite the decreasing trends of PFAS in Czechia [ 8 ], sludge was recently detected PFAS contamination in 43 wastewater treatment plants (WWTP) [ 9 ], which is a major source of PFAS pollution [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The PFAS regulation rules differ among European countries; for example, in Denmark, the use of PFAS in paper and board food packaging has been banned since July 2020, and no French fries bags exhibit PFAS; but in Czechia, these items recently showed highly persistent PFAS levels [ 4 ]. Despite the decreasing trends of PFAS in Czechia [ 8 ], sludge was recently detected PFAS contamination in 43 wastewater treatment plants (WWTP) [ 9 ], which is a major source of PFAS pollution [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…1,4,5 A significant portion of urban areas has PFAS concentrations above the EPA limits as PFAS is found in a variety of products including, but not limited to, cosmetics, firefighting foam, protective coatings ( e.g. , for automotive, aerospace, and culinary applications), and consumer packaging 6–8 (see Panieri et al 8 for a more comprehensive listing). It has been demonstrated that contamination occurs through soil and groundwater sources 3,9–17 and leads to accumulation in local food chains, 18,19 oceans 20 and prenatally in humans.…”
Section: Introductionmentioning
confidence: 99%
“…However, these fluorochemicals were developed to be resistant to chemical degradation; 10,24 as such they are notoriously difficult to transform which contributes to their ability to persist in the environment and their tendency to bioaccumulate. 8 Remediation techniques have been the focus of several reviews in recent years, 17,24–35 and can broadly be characterized into two paradigms: degradation and capture. It should be stressed that the debate over whether it is better to mobilize, immobilize, degrade, or some combination thereof is an active question.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to PFASs can occur via dietary intake (by consuming PFASs-contaminated water or food), dermal contact or inhalation (Domingo and Nadal, 2017;Buck et al, 2011). Major concern about human health effects of persistent PFASs led to an adjustment in their application and to a reduction in their use in consumer products, but still about 470 t of non-polymeric PFASs were used in flame retardants and extinguishing agents between 2000 and 2017 in the Nordic countries of Europe alone (Panieri et al, 2022;Glüge et al, 2020). Some PFASs have half-lives on the order of years in the human body (Brede et al, 2010;Seals et al, 2011) and have been associated with developmental delays in the foetus and child (Blake and Fenton, 2020), decreased fertility (Chambers et al, 2021), and changes in endogeneous hormones, increased cholesterol levels, changes to the immune system, increased uric acid levels, changes in liver enzymes, and prostate, kidney and testicular cancer (Panieri et al, 2022).…”
Section: Introductionmentioning
confidence: 99%